2011
DOI: 10.1002/app.33815
|View full text |Cite
|
Sign up to set email alerts
|

Rice hull biocomposites, part 2: Effect of the resin composition on the properties of the composite

Abstract: A free radical thermoset resin consisting of a copolymer of conjugated linseed oil (CLO) or conjugated soybean oil (CSO), n-butyl methacrylate (BMA), divinylbenzene (DVB), and maleic anhydride (MA) has been reinforced with rice hulls. Composites containing 70 wt % of the filler were compression molded, the conjugated oil content in the resin was kept constant at 50 wt %, and the relative amounts of BMA, DVB, and MA were varied to afford composites with different resin compositions. Tensile tests, DMA, thermogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 26 publications
10
40
0
Order By: Relevance
“…These results support the idea that a higher number of carbon–carbon double bonds in the oil (linseed oil has on average 6.0 carbon–carbon double bonds per triglyceride, while soybean oil only possesses 4.5 carbon–carbon double bonds per triglyceride) gives a more crosslinked and stronger material. A similar trend has been observed and recently published by us for soybean and linseed oil‐based rice hull composites 33. As for the Young's modulus of the CSO‐ and CLO‐based composites compared here (entries 2 and 5, Table III), the values measured fall within the standard deviation of the method used and therefore cannot be considered statistically different.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…These results support the idea that a higher number of carbon–carbon double bonds in the oil (linseed oil has on average 6.0 carbon–carbon double bonds per triglyceride, while soybean oil only possesses 4.5 carbon–carbon double bonds per triglyceride) gives a more crosslinked and stronger material. A similar trend has been observed and recently published by us for soybean and linseed oil‐based rice hull composites 33. As for the Young's modulus of the CSO‐ and CLO‐based composites compared here (entries 2 and 5, Table III), the values measured fall within the standard deviation of the method used and therefore cannot be considered statistically different.…”
Section: Resultssupporting
confidence: 90%
“…The presence of ligno‐cellulosic filler particles minimizes shrinkage of the resin and only minimal microcracks have been detected by scanning electron microscopy (SEM) of soybean hull composites 30. Recent results from the study of natural filler‐reinforced composites in the Larock group suggested that maleic anhydride (MA) can serve as a good filler‐resin compatibilizer and help improve the stress transfer from the matrix to the reinforcement, resulting in an overall increase of the mechanical properties 32, 33…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…91,92 In addition, the free radical polymerization of conjugated soybean or linseed oil, divinylbenzene, and n-butyl methacrylate produced thermosets used as matrixes for biocomposites reinforced with soy hull, 93 corn stover, 94 and rice hulls. 95,96 Maleic anhydride was added to serve as an additional comonomer to prepare biocomposites reinforced with wood Chem. Rev.…”
Section: Plant Oils For the Synthesis Of Hyperbranched And Crosslinkementioning
confidence: 99%